Craniocerebral involvement in lymphoma - Jorge D. Correale; David A. Monteverde; José A. Bueri; Edgardo G. Reich; Néstor Lucatelli (Arquivos de Neuro-Psiquiatria)
Nine-hundred-eighty-nine patients with lymphoma were studied. Fifty-three cases (5.3%) had lymphomatous craniocerebral infiltration. The principal factors of risk for this complication were: advanced stage of the lymphoma (III or IV), diffuse histiocytic, diffuse poorly differentiated lymphocytic, or mixed cellularity lymphoma histological type, bone marrow involvement, and previous systemic chemotherapy. Thirty-two per cent of the cases of meningeal lymphomatous infiltration were asymptomatic and represented autopsy findings. CT-scan was an useful test to detect brain focal parenchymatous infiltration, as opposed to meningeal infiltration. Mean survival time in patients with lymphomatous meningeal infiltration was 4.3 months, following the combined use of systemic chemotherapy, radiation therapy and intrathecal methotrexate. Two cases had primary cerebral lymphoma, although without associated immunodeficiency Twenty patients (2%) had intracranial hemorrhage, in clear relationship with platelet alterations. Fifteen patients (1.5%) had CNS infection, caused by common bacteriae or opportunistic agents. In 7 cases, the diagnosis was made at autopsy. Thirty-six autopsies were performed. In 8 cases (22%), pathologic findings such as, demyelination, microcalcificat ons, coagulative necrosis, or gliosis, suggested complications from treatment.